Theorising creative industry management: rebooting the woolly mammoth - Pick, David; Weber, Paull; Connell, Julia; Geneste, Louis (Emerald, 2015)
Purpose – The purpose of this paper is to highlight the paradox inherent in the term “Creative Industry Management”. The challenges of applying creative industry experiences within a managerial context are explored through a careful selection of papers that identify linkages between creative industry practice and management theories. Design/methodology/approach – The paper is a narrative commentary using the Jurassic Park franchise to highlight the potential application of management theory to explain the success or failure of a creative venture. The analogy of filmmaking and the creation of blockbuster movie sequels is useful in determining the tensions between creative production and management of a profitable franchise. Findings – This paper identifies opportunities for theory building at the meso level in the management domain, born of the experiences of those in the creative industries. The papers presented add to the continuing discovery of ways of applying management theory in the creative industries. However, there remain opportunities for a cross-pollination of theory from the creative industry to management domains. Research limitations/implications – It is not possible to claim more than observation and exploratory inference from the selection of papers presented. The special issue has only uncovered one half of the theoretical perspective, namely management theory that can be applied in the creative industries. Originality/value – The approach taken to liken the challenge of managing creativity to the production of creative works in moviemaking is novel and highlights the dearth of creative industry experiences that currently influence management theory.